The Toxicological Effects of Glyphosate on Hematological and Genotoxic Parameters in Coturnix japonica (Japanese Quail) - Ubaidullah; Shah, Nazish; Khisroon, Muhammad; Aamir, Muammad (Indus Journal of Bioscience Research, 2025)
Significant ecological and environmental issues have emerged due to the increased use of agrochemicals to meet the food demands of a growing population. In the agricultural industry, glyphosate is widely applied to various food crops. However, prolonged exposure to this chemical has been associated with serious endocrine-disrupting effects in animals, along with potential health implications for humans. This study aimed to evaluate the hematological and genotoxic effects of glyphosate in Japanese quail (Coturnix japonica). A total of 18 adult quails were obtained and randomly divided into four groups (A–D). Glyphosate was administered orally for 21 days. Group A served as the control, while groups B, C, and D received glyphosate at doses of 334.0 mg/kg, 33.40 mg/kg, and 3.340 mg/kg body weight, respectively. The results revealed significant hematological abnormalities, including anemia, thrombocytopenia, and oxidative stress. Red blood cell (RBC) count and hemoglobin (Hb) levels showed a marked decline over time in the higher exposure groups. These findings corroborate earlier studies indicating glyphosate’s toxic effects across various species and underscore the potential ecological risks posed by its widespread use.